(untitled) (Journal of Enam Medical College, 2016)
Transformer oil is one kind of highly refined oil which is used as coolant and heat exchanger in different electronic equipments. Poisoning with this oil is a rare type of chemical poisoning as it is not easily available for household purpose. The main constituent of transformer oil is polychlorinated biphenyl (PCB) which is responsible for producing toxicity in humans. Chronic exposure with PCB may cause some toxicity such as hepatotoxicity and neurotoxicity. Here we present a case of acute toxicity with transformer oil of a rural woman in Bangladesh who ingested this oil as suicidal attempt. She was managed efficiently through conservative treatment along with artificial ventilation. J Enam Med Col 2016; 6(2): 110-113